2013
DOI: 10.4269/ajtmh.12-0464
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Glycerol-3-Phosphate Dehydrogenase Isoforms in Flight Muscles of the Chagas Disease Vector Triatoma infestans (Hemiptera, Reduviidae)

Abstract: Abstract. Flight muscles of Triatoma infestans have two glycerol-3-phosphate dehydrogenase (GPDH) isoforms: GPDH-1 is involved in flight metabolism and GPDH-2 provides lipid precursors. Total GPDH activity was greater in the natural population and almost only due to GPDH-1. Different expression and activity observed between GPDH isoforms in the natural population and the first laboratory generation was not detected in the second laboratory generation. This pattern may be caused by gradual adaptation to laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…26 In another study, we showed that GPDH-1 and GPDH-2 exhibited a tissue-specific pattern of expression and differentiated by sex and that the expression pattern of GPDH changes with different temperatures and amount of intake. 27 These results were consistent with transcripts requirement for GPDH isozymes expression according to the metabolic role described for GPDH isozymes in flying insects. 23,24 Daily rhythms have been observed in a wide variety of behavioral, physiological, and metabolic process in many insects.…”
Section: Introductionsupporting
confidence: 79%
“…26 In another study, we showed that GPDH-1 and GPDH-2 exhibited a tissue-specific pattern of expression and differentiated by sex and that the expression pattern of GPDH changes with different temperatures and amount of intake. 27 These results were consistent with transcripts requirement for GPDH isozymes expression according to the metabolic role described for GPDH isozymes in flying insects. 23,24 Daily rhythms have been observed in a wide variety of behavioral, physiological, and metabolic process in many insects.…”
Section: Introductionsupporting
confidence: 79%
“…It was demonstrated that GPDH isoforms present a pattern of temporal expression, tissue-specific, differentiated by sex, and show changes in relation to temperature and the amount of intake. 22,23 In flight muscles of adult T. infestans under different conditions of photoperiod, the expression of GPDH isoforms presented rhythmic variations differentiated by sex. 24 GPDH-1, the isoform involved in the energetic metabolism of the flight, showed a rhythmic expression profile and synchronized in constant darkness, suggesting an endogenous clock regulation.…”
Section: Introductionmentioning
confidence: 99%